Ask a Statistician: Does Manchester United really have 100 million followers in China?. Issue 3 (29th May 2019) - Mastrodomenico, Rob
Abstract : A reader writes: I was interested to see a Times article about some new Manchester United‐themed centres that will be built in China. In the football club's associated press release, it claims to have "100 million followers" in China. This is, interestingly, 8 million fewer than the figure it claimed to have back in 2012. Is there any truth to these figures? Abstract : A reader writes: I was interested to see a Times article about some new Manchester United‐themed centres that will be built in China. In the football club's associated press release, it claims to have "100 million followers" in China. This is, interestingly, 8 million fewer than the figure it claimed to have back in 2012. Is there any truth to these figures?